1998
DOI: 10.1046/j.1440-1738.1998.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic implications of new age data for the Meratus Complex of south Kalimantan, Indonesia

Abstract: Cretaceous subduction complexes surround the southeastern margin of Sundaland in Indonesia. They are widely exposed in several localities, such as Bantimala (South Sulawesi), Karangsambung (Central Java) and Meratus (South Kalimantan). The Meratus Complex of South Kalimantan consists mainly of mélange, chert, siliceous shale, limestone, basalt, ultramafic rocks and schists. The complex is uncomformably covered with Late Cretaceous sedimentary‐volcanic formations, such as the Pitap and Haruyan Formations. Well‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 14 publications
1
49
0
7
Order By: Relevance
“…However, most of species member within these assemblage are different with those in the Barru Complex, except for Pseudodic tyomitra carpatica and Pantanellium squinaboli. Wakita et al (1998) also found manganese carbonate nodule in melange of Laut Island, but lack of radiolarian or very poorly preserved. This difference may be influenced by sedimentation environment and/or paleo-current that bring nutrient for radiolarians life.…”
Section: )mentioning
confidence: 87%
See 2 more Smart Citations
“…However, most of species member within these assemblage are different with those in the Barru Complex, except for Pseudodic tyomitra carpatica and Pantanellium squinaboli. Wakita et al (1998) also found manganese carbonate nodule in melange of Laut Island, but lack of radiolarian or very poorly preserved. This difference may be influenced by sedimentation environment and/or paleo-current that bring nutrient for radiolarians life.…”
Section: )mentioning
confidence: 87%
“…Radiolarian assemblage of the similar age to that in Barru Complex is also occur in Laut Island, Meratus Complex in South Kalimantan (Wakita et al, 1998). Radiolarians in Laut Island were extracted from chert and siliceous shale in the melange.…”
Section: )mentioning
confidence: 96%
See 1 more Smart Citation
“…-Scattered occurrences of Jurassic and Cretaceous mélange yielding bedded radiolarian cherts, as well as limestones, basalt and ophiolitic rock types occur in the Lok Ula Complex on Java, the Meratus Complex on Kalimantan and the Bantimala Complex on Sulawesi (Wakita 2000;Wakita et al 1998. Pessagno & Hull (2002) described Northern Austral Province Oxfordian radiolarians from the Sula Islands, close to eastern Sulawesi.…”
Section: Dynamic Oceansmentioning
confidence: 99%
“…Rosidi et al 1976). In SE Borneo there are andesitic lavas, tuffs and volcanic breccias that are assigned entirely to the Haruyan Formation by Wakita et al (1998) or placed within the Alino Group by Sikumbang & Heryanto (1994) and Yuwono et al (1988) that are interpreted to represent a volcanic arc suite. These lithologies are approximately Late Aptian to Cenomanian in age (115 -93.5 Ma) (Yuwono et al 1988;Wakita et al 1998).…”
Section: Plutonic and Volcanic Rocksmentioning
confidence: 99%